BCL11A deletions result in fetal hemoglobin persistence and neurodevelopmental alterations - Basak, Anindita (J Clin Invest, 2015)
A transition from fetal hemoglobin (HbF) to adult hemoglobin (HbA) normally occurs within a few months after birth. Increased production of HbF after this period of infancy ameliorates clinical symptoms of the major disorders of adult β-hemoglobin: β-thalassemia and sickle cell disease. The transcription factor BCL11A silences HbF and has been an attractive therapeutic target for increasing HbF levels; however, it is not clear to what extent BCL11A inhibits HbF production or mediates other developmental functions in humans. Here, we identified and characterized 3 patients with rare microdeletions of 2p15-p16.1 who presented with an autism spectrum disorder and developmental delay. Moreover, these patients all exhibited substantial persistence of HbF but otherwise retained apparently normal hematologic and immunologic function. Of the genes within 2p15-p16.1, only BCL11A was commonly deleted in all of the patients. Evaluation of gene expression data sets from developing and adult human brains revealed that BCL11A expression patterns are similar to other genes associated with neurodevelopmental disorders. Additionally, common SNPs within the second intron of BCL11A are strongly associated with schizophrenia. Together, the study of these rare patients and orthogonal genetic data demonstrates that BCL11A plays a central role in silencing HbF in humans and implicates BCL11A as an important factor for neurodevelopment.